Revival of Sri Lankan Wildlife Tourism Operation in New Normal Conditions of Covid -19: Challenges and Readiness - H.P.P.M. Pathiraja; A.C.I.D. Karunarathne; Vindya Hewage; H.N. Jayawardena (Journal of Sustainable Tourism and Entrepreneurship, 2022)
Purpose: Wildlife tourism industry as a form of nature-based tourism was a rapidly growing niche market segment & has developed a revenue platform for many economies. Outstretching the Pandemic of COVID-19, badly hit with wildlife tourism sector too. Nevertheless, it is a contemporary need to rejuvenate the current market segments to reconstruct tourism industry potentials. This study explores the ways and means to revival of wildlife tourism operations with the challenges of COVID-19. Methodology/approach: This study used a qualitative research approach. Primary data was collected from 16 wildlife service providers at Minneriya national park using the purposive sampling technique. Content analysis was used to analyze the data. Results/findings: The study's findings revealed operational, financial, labor-related, communication, technology & economic impact as the existing challenges in wildlife tourism operations during pandemics & introducing recreational activities, health & safety measures, technology, policy planning, etc. should be key priorities to revive the wildlife tourism sector in a post-COVID-19 scenario. Limitations: The study limited to the Minneriya National Park and given the number of existing national parks in Sri Lanka, the geographical region is comparatively smaller. Contribution: The outcome of this study recommends the Sri Lankan policy makers to identify the gaps to promote wildlife tourism from the perspective of service providers. The pandemic has created a sustainable platform to rejuvenate the wildlife tourism which it has been enabled to address the issues in long-term. Novelty: Based on the results, there should be strong transformational strategies to avoid the worst effects of future operation: such as government involvement, financial facilities, promotions, and research & development. This study identified a response mechanism to attract travelers to achieve a niche market segment. It will manifest the significance to the future generation, policymakers, and academic students to grab value scale for future operation in new normal conditions and post-COVID-19.